Prevalence and Risk Factors of Acute Respiratory Infections among Under-Five Children in Urban Slums of North Kerala - George, Ardra Merin; Sivakumar CP; George, Biju; Athira T (National Journal of Community Medicine, 2026)
Background: Acute respiratory infections (ARI) are a leading cause of morbidity and mortality among under-five children, particularly in urban slum settings. Evidence from Kerala's urban slums remains limited, necessitating context-specific research. Methods: A community-based cross-sectional study was conducted across ten urban slums of Kozhikode Municipal Corporation from July 2020 to July 2021. Using cluster sampling, 150 children aged ≤5 years were enrolled. ARI prevalence was assessed using two-week symptom recall. Associations between risk factors and ARI were evaluated using chi-square tests and odds ratios. Results: ARI prevalence was 38% (95% CI: 23.3–55.1%), with upper respiratory tract infections predominating (75.4%). Birth order greater than two (OR: 2.4; p=0.03), contact with an ARI case (OR: 5.8; p=0.017), and low maternal educational status (OR: 2.6; p=0.008) showed significant associations in bivariate analysis. However, no independent predictor was identified in multivariate logistic regression. Conclusion: ARI burden among under-five children in urban slums is shaped by overlapping sociodemographic determinants. Targeted interventions addressing maternal education, household exposure reduction, and improved surveillance are essential to mitigate ARI in vulnerable urban populations.